Grid Model Reduction for Large Scale Renewable Energy Integration Analyses. (2015) - Svendsen, Harald G.
Abstract: This paper provides a brief description of an algorithm for generating equivalent, reduced power flow models. It presents the underlying principles and the various steps of the reduction process. The procedure is applied to two different cases: The Moroccan power system and the Norwegian power system. The derived reduced, equivalent models are briefly discussed and compared with the full models. The model reduction procedure and its implementation as Matlab / Python scripts is generic and may be applied for reduction of any grid model described by a PSSE load flow file.